(untitled) (Research, Society and Development, 2021)
Taking into account the importance of including students with disabilities in Physical Education classes, the study aimed to investigate the process of inclusion in classes of this Curriculum Component in a riverside school located on Ilha do Combu, in Belém do Pará. , a survey was carried out based on the qualitative approach. Data collection was used through a semi-structured interview with a student with a disability. For data interpretation, content analysis was performed. The results showed a lack of accessibility for boarding and disembarking students with disabilities. The inadequate infrastructure of the school and spaces used in Physical Education classes. The need for specific or continued training for teachers. It was concluded that there is a need to implement effective public policies that address riverside education that actually enable the inclusion of students with disabilities, especially in Physical Education classes. Therefore, this study can encourage more research in this universe, contributing to the strengthening of the praxis related to the inclusion of students who are marginalized due to disabilities.